FEASIBILITY OF STUDENT’S WORKSHEET ORIENTED GUIDED DISCOVERY ON PTERIDOPHYTA AT TENTH GRADE OF HIGH SCHOOL - DWI FERDIYANTI, SEPTYANA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
The purpose of this study is to produce of students worksheet oriented guided discovery on Pteridophyta which is feasible theoritically and empirically by validation and student’s responses. This research was developmental research which developed guided discovery student’s worksheet by 4-D method (without disseminate phase). The result showed that the guided discovery student’s worksheet have been developed was feasible, both theoritically and empirically. The worksheet got good result, because the validation result showed that 95,50%. The worksheet was also good empirically student’s response was 86,50% Keywords: Student’s worksheet, Guided discovery, Pteridophyta, Ten Grade